Applied logic: A mastery learning approach delivered fully online (International Conference on Computers in Education, 2020)
This paper describes the move to a web-based mastery approach in an elective course on applied logic offered in a public university in northern Japan. This fully online course is designed using a content and language integrated approach so that students learn both the content and English at the same time. Logical and critical thinking is laden with complex concepts and technical terminology, and so to increase the rate and degree of comprehension, a mastery learning approach was adopted. An inventory of concepts, technical terminology and skills was created. The mastery list was sequenced into concept chains moving from lower to higher level concepts. Active learning activities were created for each concept chain. Criterionbased assessment checklists were created to enable self, peer and teacher assessment. Student response to the detailed mastery list was extremely positive. Using this mastery list students were better able to monitor their progress and identify which concepts to study